Consumer Dispute Resolution in the Financial Services Sector in Indonesia - Agus Satory; Sufmi Dasco Ahmad; Roby Satya Nugraha (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
The purpose of this study is to analyze the model of consumer dispute resolution in the financial services sector in Indonesia. The research method used in this study is a normative juridical approach supported by empirical data. Consumer disputes can be resolved through the courts or out of court based on the voluntary choice of the disputing parties. This means that consumers are given the freedom to claim their rights if they are harmed by business actors, either through litigation or non-litigation channels. Thus, consumers in the financial services sector who have been harmed can choose from the current models of consumer dispute resolution in the financial services sector, namely litigation through breach of contract suits, unlawful act suits, class actions, legal standing, and small claims courts. Meanwhile, non-litigation can be pursued through BPSK, LAPS SJK, or LAPS SK. The use of the small claims court mechanism as one of the models for resolving consumer disputes in the financial services sector through litigation in court can be empowered, and the process of resolving consumer disputes through non-litigation via BPSK can be carried out in stages.